2020
DOI: 10.2480/agrmet.d-20-00027
|View full text |Cite
|
Sign up to set email alerts
|

Bias correction for spatially interpolated daily mean air temperature during winter in eastern Hokkaido using multimodal machine learning

Abstract: Interactions between boundary layer wind and topography form non-uniform air temperature distributions in cold and snow-covered regions. Because of this heterogeneity, spatially interpolated air temperatures sometimes deviate from observed values. To evaluate the quality of spatially interpolated daily mean temperatures T int provided by a 1 km gridded meteorological data service Ohno et al., 2016 , we collected observed temperatures T obs obtained at meteorological observation sites located near farmland in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In northern Japan, rainfall in December is expected to increase and snowfall is expected to decrease in the future (Inatsu et al 2016, Kawase et al 2021, which could lead to widespread implementation in regions previously unimplemented. Refinement of winter weather information (Fukushima et al 2019, Murakami et al 2020, Yazaki et al 2017 will also contribute to the advancement of snow compacting operations in the future. Previous studies have shown that soil frost can be useful for the efficient use of water resources and nitrogen in natural ecosystems (Fukuzawa et al 2021, Makoto et al 2014) and agricultural fields (Iwata et al 2018, Onodera et al 2022, Yanai et al 2011.…”
Section: Future Considerationsmentioning
confidence: 99%
“…In northern Japan, rainfall in December is expected to increase and snowfall is expected to decrease in the future (Inatsu et al 2016, Kawase et al 2021, which could lead to widespread implementation in regions previously unimplemented. Refinement of winter weather information (Fukushima et al 2019, Murakami et al 2020, Yazaki et al 2017 will also contribute to the advancement of snow compacting operations in the future. Previous studies have shown that soil frost can be useful for the efficient use of water resources and nitrogen in natural ecosystems (Fukuzawa et al 2021, Makoto et al 2014) and agricultural fields (Iwata et al 2018, Onodera et al 2022, Yanai et al 2011.…”
Section: Future Considerationsmentioning
confidence: 99%